Bibliographic Review of Lexical Availability Studies in Central America: Costa Rica, Guatemala, Panama and El Salvador - Herranz-Llácer, Cristina V. (2023)
This article aims to present a systematic descriptive bibliographic review of the lexical availability developed in Central America from its beginnings to the present. The research was carried out based on Dialnet, Scielo, Google Scholar, and DispoLex. Thanks to this research, it can be affirmed that studies on lexical availability in Costa Rica present a strong tradition. In Guatemala, Panama, and El Salvador, research on this field is at an early stage (few publications have been located). And, in the case of Nicaragua and Honduras, the research has not been yet initiated (there are no works published). This article, therefore, presents an initial bibliographic control tool that ambitions to expose, on the one hand, the situation of each of the countries mentioned and, on the other hand, the particularities of the research located, as well as their contributions to lexical availability.